(untitled) (Preventif : Jurnal Kesehatan Masyarakat, 2020)
Traffic accidents are still a global problem today. Traffic accidents are the main cause of death for all age groups dominated by adolescents. The number of traffic accident cases in Indonesia reached 108,871 incidents with details of which 25,511 people died. Accident data in Central Sulawesi during 2016 reached 1,889 incidents, with 420 dead, 1,076 serious injuries and 2,042 minor injuries. The city of Palu is in order no. 1 with traffic accidents 308 cases with losses of up to 616 million rupiah. The purpose of this study was to determine the factors associated with safety riding behavior. This type of research is quantitative with a Cross Sectional Study approach, sampling using the Proportional Stratified Random Sampling method. The number of samples in this study were 84 respondents. The data were collected using a questionnaire with a Guttman scale. The data obtained were analyzed statistically using the Chi-Square test. The results showed that there was no relationship between knowledge (p = 0.95), while there was a relationship between attitude (p = 0.008), SIM ownership (p = 0.003), and safety riding behavior. To prevent traffic accidents, it is necessary to provide an understanding of Safety Riding, guide traffic discipline, invite them to complete driving licenses, familiarize children with using PPE, and provide motivation to always prioritize safety in driving.